2007
DOI: 10.1111/j.1365-2850.2007.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction in psychiatric nursing

Abstract: In recent years, mental health services across Europe have undergone major organizational change with a move from institutional to community care. In such a context, the impact of change on the job satisfaction of psychiatric nurses has received little attention in the literature. This paper reports on the job satisfaction of psychiatric nurses and data were collected in 2003. The population of qualified psychiatric nurses (n = 800) working in a defined geographical health board area was surveyed. Methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 41 publications
1
51
0
2
Order By: Relevance
“…The impact of stress, burnout, and job satisfaction in mental health nursing, have generally been considered in relation to the broader workforce issues of recruitment and retention. (Clinton, 2000;Clinton & Hazelton, 2000;Currid, 2008;Happell, 2008;Nakakis & Ouzouni, 2008;Ward & Cowman, 2007). The rationale being that the less mental health nurses feel burnt out and the more satisfied they feel with their work, the more likely the are to remain in the field, and the more likely it is that mental health nursing will be considered an attractive career option to others.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The impact of stress, burnout, and job satisfaction in mental health nursing, have generally been considered in relation to the broader workforce issues of recruitment and retention. (Clinton, 2000;Clinton & Hazelton, 2000;Currid, 2008;Happell, 2008;Nakakis & Ouzouni, 2008;Ward & Cowman, 2007). The rationale being that the less mental health nurses feel burnt out and the more satisfied they feel with their work, the more likely the are to remain in the field, and the more likely it is that mental health nursing will be considered an attractive career option to others.…”
Section: Discussionmentioning
confidence: 95%
“…Mental health nursing has been acknowledged as a highly stressful profession, often accompanied by relatively low levels of job satisfaction and high levels of burnout (Clinton, 2000;Clinton & Hazelton, 2000;Currid, 2008;Happell, 2008;Nakakis & Ouzouni, 2008;Ward & Cowman, 2007). To date, however, most of the literature has focused on the implications of stress, burnout, and job satisfaction on the recruitment and retention of the mental health nursing workforce.…”
mentioning
confidence: 97%
“…Generally considered to be an individual's perceptual/emotional reaction to important facets of work [18]. Job satisfaction describes how we feel about a job [19] is a positive affective orientation toward employment [20,21]. Like other emotional judgments, job satisfaction arises from a variety of feelings related to the characteristics of the job, like feelings about the working conditions [22].…”
Section: Job Satisfaction As An Affectmentioning
confidence: 99%
“…Unlike the ward atmosphere, with its focus on treatment and patients, the psychosocial work environment emphasizes the situation for the nursing staff, in terms of organizational conditions for their work and relational aspects among the nursing staff and between staff and managers. Previous research in psychiatric care has shown that the psychosocial work environment is vital for the staffs' job satisfaction, 18,19 and is important in relation to stress. 15,20 The psychosocial work environment has also found to be related to nurses' moral sensitivity, 21 and low staffing levels have shown to be associated with moral distress among Japanese psychiatric nurses.…”
Section: Introductionmentioning
confidence: 99%